2011
DOI: 10.1093/jxb/err259
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-sensing receptor regulates stomatal closure through hydrogen peroxide and nitric oxide in response to extracellular calcium in Arabidopsis

Abstract: The Arabidopsis calcium-sensing receptor CAS is a crucial regulator of extracellular calcium-induced stomatal closure. Free cytosolic Ca2+ (Ca2+i) increases in response to a high extracellular calcium (Ca2+o) level through a CAS signalling pathway and finally leads to stomatal closure. Multidisciplinary approaches including histochemical, pharmacological, fluorescent, electrochemical, and molecular biological methods were used to discuss the relationship of hydrogen peroxide (H2O2) and nitric oxide (NO) signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 59 publications
(112 reference statements)
3
78
1
Order By: Relevance
“…S15 ), suggesting a limited role of NADPH oxidase-derived O 2 − and H 2 O 2 in CAS-dependent immune responses. In addition, it has been recently shown by another group that extracellular Ca 2 + -induced generation of chloroplast NO and ROS is dependent on CAS, but not plasma membrane-localized NADPH oxidase 35 , providing further confi rmation of the role of CAS in ROS production in chloroplasts. Th us, we assume that CAS may be involved in the chloroplast-derived 1 O 2 -mediated retrograde signalling that regulates the expression of nuclear-encoded defence-related genes at an early stage in PTI.…”
Section: Days After Inoculation ( D ) Ion Leakage At 3 Days After Inmentioning
confidence: 80%
“…S15 ), suggesting a limited role of NADPH oxidase-derived O 2 − and H 2 O 2 in CAS-dependent immune responses. In addition, it has been recently shown by another group that extracellular Ca 2 + -induced generation of chloroplast NO and ROS is dependent on CAS, but not plasma membrane-localized NADPH oxidase 35 , providing further confi rmation of the role of CAS in ROS production in chloroplasts. Th us, we assume that CAS may be involved in the chloroplast-derived 1 O 2 -mediated retrograde signalling that regulates the expression of nuclear-encoded defence-related genes at an early stage in PTI.…”
Section: Days After Inoculation ( D ) Ion Leakage At 3 Days After Inmentioning
confidence: 80%
“…Numerous studies have demonstrated chloroplastic ROS accumulation following ABA treatment (Pei et al, 2000;Zhang et al, 2001b), extracellular Ca 2+ (Nomura et al, 2008;Wang et al, 2012), ozone (Joo et al, 2005;Vahisalu et al, 2010), and other stimuli leading to stomatal closure. Following these discoveries, hypotheses of the regulatory role of chloroplast-dependent ROS accumulation in stomatal movements have been drawn (Sierla et al, 2013).…”
Section: The Interplay Between Apoplastic and Intracellular Ros Produmentioning
confidence: 99%
“…53 Indeed, several genes related to ABA signalling were overrepresented under high Cu conditions (Table S1, ESI †). Moreover Ca 2+ fluxes and ROS production have already been reported to participate in both Cu signalling 54 and circadian rhythm regulation.…”
Section: Defining Nutritional Cu Ranges At the Molecular Levelmentioning
confidence: 99%